Clinical and laboratory features of patients with pericardial effusion [Perikart efüzyonu olan hastalarin klinik ve laboratuvar özellikleri] - (:unkn) unknown (My University, 2010)
Objectives: We reviewed patients who were diagnosed to have pericardial effusion (PE) over a four-year period to determine the causes of PE, clinical and laboratory features, and treatment modalities. Study design: Medical records of 136 patients (81 women, 55 men; mean age 55.8±18.7 years; range 8 to 90 years) admitted to our department with PE from August 2005 to August 2009 were reviewed. The diagnosis of PE was made by transthoracic echocardiography. Medical history, physical examination, electrocardiography, echocardiography, and laboratory findings and treatment methods were recorded. Results: The most frequent complaint was dyspnea (86.8%) and the most common physical examination finding was jugular venous distension (47.1%). The most common electrocardiographic and echocardiographic findings were tachycardia (47.8%) and mild PE (<1 cm) (63.2%), respectively. Chronic renal failure and malignant diseases were the primary causes of PE (25% and 22.8% respectively), followed by idiopathic cases (14%). Pericardial tamponade was detected in 34 patients (25%), of which the majority had malignant diseases (53%). Thirty-eight patients (27.9%) underwent interventional treatment (pericardiocentesis in 27, surgical drainage in 11), while 98 patients (72.1%) were followed-up with medical treatment. Mortality occurred in three patients with pericardial tamponade. Conclusion: The most common causes of PE in our cases were chronic renal failure and malignancies. The incidence of malignant PE is on the incline owing to increased life expectancy. Echocardiography is the primary imaging modality for the evaluation of PE.
Keywords: Cardiac tamponade/etiology; Chronic/complications; Echocardiography; Kidney failure; Pericardial effusion/etiology; Pericardiocentesis; Pericarditis; Tuberculous